ChatGPT as an Educative and Pedagogical Tool: Perspectives and Prospects in International Schools in Indonesia - Maspul, Kurniawan Arif; Chemistry, Valerie Indiana; Melinda, Yona; Wisudayanti, Karila; Fedora; Rochmah, Dwi Febriana (Indonesian Journal Publisher, 2025)
In an era where artificial intelligence is redefining the global educational landscape, Indonesia stands at a critical juncture—torn between opportunity and inequity. This study explores the transformative potential of ChatGPT as an educative and pedagogical tool in international schools across the Indonesian archipelago, highlighting its promise to personalize learning, reduce teacher burnout, and democratize access to knowledge. Yet, this promise is tempered by systemic barriers: rural-urban divides, limited infrastructure, fragmented policy, and cultural misalignments. Through a qualitative, multi-site investigation grounded in constructivist and connectivist theories, the study captures the real-world integration of AI in Indonesian classrooms—where innovation often outpaces regulation. Data from pilot programs and classroom observations reveal that, when localized and ethically scaffolded, ChatGPT can enhance student engagement, foster cognitive autonomy, and empower teachers as co-designers of learning. However, without national strategies to ensure equity, inclusivity, and ethical oversight, AI risks becoming a new vector for educational disparity. This paper offers a bold roadmap for action—centering on teacher training, infrastructure justice, and culturally embedded AI policies—to ensure that ChatGPT does not become a privilege of the few, but a transformative catalyst for all. In Indonesia’s hands, AI need not be a mirror of global inequality; it can become a beacon of inclusive, human-centered education.